Xanthine Oxidoreductase: A Double-Edged Sword in Neurological Diseases - Massimo Bortolotti; Letizia Polito; Maria Giulia Battelli; Andrea Bolognesi (Antioxidants)
Non-communicable neurological disorders are the second leading cause of death, and their burden continues to increase as the world population grows and ages. Oxidative stress and inflammation are crucially implicated in the triggering and progression of multiple sclerosis, Alzheimer’s disease, amyotrophic lateral sclerosis, Huntington’s disease, Parkinson’s disease, and even stroke. In this narrative review, we examine the role of xanthine oxidoreductase (XOR) activities and products in all the above-cited neurological diseases. The redox imbalance responsible for oxidative stress could arise from excess reactive oxygen and nitrogen species resulting from the activities of XOR, as well as from the deficiency of its main product, uric acid (UA), which is the pivotal antioxidant system in the blood. In fact, with the exception of stroke, serum UA levels are inversely related to the onset and progression of these neurological disorders. The inverse correlation observed between the level of uricemia and the presence of neurological diseases suggests a neuroprotective role for UA. Oxidative stress and inflammation are also caused by ischemia and reperfusion, a condition in which XOR action has been recognized as a contributing factor to tissue damage. The findings reported in this review could be useful for addressing clinical decision-making and treatment optimization.